RESPON SUAMI TERHADAP KEHAMILAN ISTRI (STUDI DI KELURAHAN TANGKERANG TENGAH KOTA PEKANBARU) - Dina Mariana; Yoskar Kadarisman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
In the process of the wife pregnancy, the husband's concern is important. The attention given by the husband will affect the physical and psychological condition of the wife. The attention given by the husband can be seen from the husband's knowledge relating to pregnancy. The focus of the problem in this study is how the husband's knowledge of the response must be made when the wife is pregnant. The benefits of this research are expected to be the development of science, especially the sociology of health. This study used a quantitative approach, look at human behavior can be predicted and social reality, objective and can be measure, this study has a type of quantitative descriptive research that aims to describe systematically, factually, and accurately about the factors and nature of the population. In this study, 814 populations and sample collection used the Slovin formula and a sample of 89 respondents. Response Theory, Response is defined as a behavior or attitude that is tangible both before detailed understanding, influence or rejection, like it or not and the use of a particular phenomenon. The objective of this research is to determine the husband's response toward the wife pregnancy..Keywords: Knowledge, Response